The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0147071
|View full text |Cite
|
Sign up to set email alerts
|

Factors Motivating Individuals to Consider Genetic Testing for Type 2 Diabetes Risk Prediction

Abstract: The purpose of this study was to identify attitudes and perceptions of willingness to participate in genetic testing for type 2 diabetes (T2D) risk prediction in the general population. Adults (n = 598) were surveyed on attitudes about utilizing genetic testing to predict future risk of T2D. Participants were recruited from public libraries (53%), online registry (37%) and a safety net hospital emergency department (10%). Respondents were 37±11 years old, primarily White (54%), female (69%), college educated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
1
12
0
2
Order By: Relevance
“…Rather, most common diseases are influenced by complex interactions among multiple genetic and environmental factors, with each single one of them only leading to minor alterations in risk (Critchley et al, 2015; Janssens et al, 2008). All in all, the complex interactions between genetic and environmental causes in the cases of most common diseases are still poorly understood, and the clinical validity and utility of DTC genetic tests are unclear (American College of Medical Genetics and Genomics, 2016; Janssens et al, 2015; Kolor et al, 2009; Wessel et al, 2016). In the context of DTC promotion, however, genetic determinism may be employed to construct preferred meanings about genetic tests to reflect the marketing agenda of DTC companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, most common diseases are influenced by complex interactions among multiple genetic and environmental factors, with each single one of them only leading to minor alterations in risk (Critchley et al, 2015; Janssens et al, 2008). All in all, the complex interactions between genetic and environmental causes in the cases of most common diseases are still poorly understood, and the clinical validity and utility of DTC genetic tests are unclear (American College of Medical Genetics and Genomics, 2016; Janssens et al, 2015; Kolor et al, 2009; Wessel et al, 2016). In the context of DTC promotion, however, genetic determinism may be employed to construct preferred meanings about genetic tests to reflect the marketing agenda of DTC companies.…”
Section: Discussionmentioning
confidence: 99%
“…The results that current DTC genetic tests are able to provide are thus probabilistic rather than definitive in nature (Bloss et al, 2010). These results can only lead to modest or minimal changes in disease risk management (Goldsmith et al, 2012; Janssens et al, 2008), therefore the clinical validity and utility of these tests are rather limited (Agurs-Collins et al, 2015; Wessel et al, 2016). Unsurprisingly, in marketing their tests, however, the DTC companies foreground the benefits of the tests, rather than their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest polls people are interested in genetic testing for T2D risk since this allows them to evaluate the individual feature of pathology state[116]. However, several studies have shown that some factors contribute to the failure of individuals to conduct a genetic test.…”
Section: New Approaches For Clinician Interpretations Of Ngs Datamentioning
confidence: 99%
“…The main factors that influence refusal include distrust of medical researchers, religious prejudices and lower levels of education[117,118]. Some have argued that the clinical significance of genetic markers of T2D have only a minor role in predicting the risk with careful clinical risk assessment, the predictive value increases[116,119].…”
Section: New Approaches For Clinician Interpretations Of Ngs Datamentioning
confidence: 99%
“…The APT Webstudy was launched as clinical trials have increasingly utilized web-based tools, including registries, to improve efficiency in screening ( 7 9 ). Although leveraging registries to recruit for clinical trials is not a new concept, the establishment of online registries has broadened access to participants who are interested and eligible for studies ( 10 13 ). Going further than remote recruitment, Orri et al ( 14 ) conducted the first entirely web-based clinical trial run under an Investigational New Drug (IND) application.…”
Section: Introductionmentioning
confidence: 99%